Circadian Clock and The Cardiometabolic Risk - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2010)
BACKGROUND: Epidemiological data reveal parallel trends of decreasing sleep duration and increases in metabolic disorders such as obesity, diabetes and hypertension. There is growing evidence that these trends are mechanistically related.CONTENT: The circadian system orchestrates the temporal organization of many aspects of physiology, including metabolism, in synchrony with the 24 hours rotation of the Earth. The circadian system is a complex feedback network that involves interactions between the central nervous system and peripheral tissues. Circadian regulation is intimately linked to metabolic homeostasis and that dysregulation of circadian rhythms can contribute to disease. Conversely, metabolic signals also feed back into the circadian system, modulating circadian gene expression and behavior.SUMMARY: Both inter- and intraorgan desynchrony may be involved in the pathogenesis of cardiometabolic disease attributable to effects in brain and multiple metabolic tissues including heart, liver, fat, muscle, pancreas and gut. Efforts to dissect the molecular mediators that coordinate circadian, metabolic, and cardiovascular systems may ultimately lead to both improved therapeutics and preventive interventions.KEYWORDS: circadian rhythms, clock genes, nuclear receptor, sleep, obesity, cardiometabolic risk